Book Review: Leandro Herrero, (2008). Viral change: The alternative to slow, painful and unsuccessful management of change in organisations (2nd ed.) - Gray, Rodney (Public Communication Review, 2010)
Rodney Gray's Book Review of Leandro Herrero, (2008). Viral change: The alternative to slow, painful and unsuccessful management of change in organisations (2nd ed.).
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTEzMC9wY3IudjFpMi4xODcw